Binocular Diplopia in Miller Fisher Syndrome Pediatric Patient: A Rare Case Report: Poster Presentation - Case Report - Resident - Zhafira, Dinda; Prastyani, Reni; Gunawan, Prastiya Indra; Noviandi, Riza; Samosir, Sunny Mariana (Majalah Oftalmologi Indonesia, 2023)
Introduction : Miller Fisher Syndrome (MFS) is a rare variant of Guillain-Barré syndrome that usually presents with ataxia, areflexia and ophthalmoplegia. It is more common among patients in their 40s and number of cases in pediatric patients is significantly smaller. Our objective is to report a rare case of diplopia in Miller Fisher. Case Illustration : An 11 years old boy came with complaint of double vision and history of gaze restriction. Patient had history of inpatient admission due to acute progressive generalized limb weakness and walking difficulty followed by respiratory failure. Patient also had history of chewing and swallowing difficulty. Inpatient treatment included intravenous immunoglobulin (IVIG) for 5 days which resultedin clinical improvement. Electromyography examination done while hospitalization showed normal results. Orthoptic examination revealed 15 degrees exotropia of left eye with 30 prism dioptres (PD) at near and far distance. Worth four dot test resulted in cross diplopia with no abnormality in head CT scan. After 2 months follow-up with push-up pencil exercise, patient showed improvement of symptoms. Discussion : MFS is a clinical diagnosis that can be assessed by clinical triad of ataxia, areflexia and ophthalmoplegia. Diagnosis can be supported by ancillary test such as cerebrospinal fluid analysis, electrophysiologic studies or antibody anti-GQ1b . Treatment of MFS are mainly for supportive care with respiratory support and immunotherapy if needed in severe cases. Conclusion : The outcome of MFS is usually good with a complete recovery. The improvements generally begin within two to four weeks after the onset of neurological symptoms and complete within six months.